Wearable Sensor Device berbentuk Face Shield untuk Memonitor Detak Jantung berbasis IoT - Rizky Pratama Hudhajanto; Indra Hardian Mulyadi; Ade Ari Sandi (Politeknik Negeri Batam, 2022)
The heart is a very important part of the body. The main job of the heart is to pump blood to all parts of the body. The heart has a rhythmic beat when it is pumping blood. This rhythm varies according to the health condition of a person. Therefore, it is necessary to have a system to monitor this rhythm change. The most well-known way to detect the rhythm or speed of the heartbeat is by using sensors. This paper implements a sensing device using a heart rate sensor and an IoT device. The heart rate sensor used is the MAX30100 sensor. As the main processing is an ESP-WROOM-32 which is famous for its WIFI and Bluetooth features. All these devices are combined in a sensor box that is embedded in the faceshield. The result is a faceshield capable of monitoring heart rate and sending the data to various connected devices. The experimental results show the instrument's accuracy value of 9.68% compared to the professional Pulse Oximeter used in hospitals.